Investigation of possibility for stabilization and valorization of electric ARC furnace dust and glass from electronic waste - Ranitović M.; Kamberović Ž.; Korać M.; Gavrilovski M.; Issa H.; Anđić Z. (Science of Sintering, 2014)
This paper presents investigation of possibility for electric arc furnace dust (EAFD) and electronic waste (e-waste) valorization trough stabilization process, in order to achieve concurrent management of these two serious ecological problems. EAFD is an ineviTab. waste material coming from the electric arc furnace steel production process, classified as a hazardous waste. Furthermore, it is well known that residual materials generated in the ewaste recycling process, like LCD (Liquid crystal displays) waste glass, are not suiTab. for landfill or incineration. In this study, these two materials were used for investigation of possibility for their valorization in ceramic industry. Thus, an innovative synergy of waste streams from metallurgical and e-waste recycling industry is presented. Investigation included a complex characterization of raw materials and their mixtures, using chemical methods, optical microscopy, scanning electron microscopy, as well as methods for determining the physical and mechanical properties. Based on these results, it was found that material suiTab. for use in ceramics industry as a partial substituent of quartzite and fluxing components can be produced. Besides solving the environmental problem related to EAFD and LCD disposal, by replacement of raw materials certain economic effects can be achieved. [Projekat Ministarstva nauke Republike Srbije, br. 34033]